The Effect of Team Collaboration and Adaptability on Employee Performance at the BPSDM of the Ministry of Home Affairs - Sayyid Muhammad Atayya; Bambang Sutrisno (Dinasti International Journal of Economics, Finance & Accounting, 2025)
This study aims to determine the effect of team collaboration and adaptability on employee performance at the Human Resources Development Agency (BPSDM) of the Ministry of Home Affairs of the Republic of Indonesia. The method used in this study is a quantitative method with a multiple linear regression approach. Data were collected through questionnaires and analyzed using SPSS software version 25. The results of the analysis showed that there were no multicollinearity and heteroscedasticity problems in the regression model used. Partially, the team collaboration variable has a positive and significant effect on employee performance with a significance value of 0.053 and a t-count value of 1.960. The adaptability variable also has a positive and significant effect with a significance value of 0.000 and a t-count value of 7.410. Simultaneously, team collaboration and adaptability have a significant effect on employee performance with a calculated F value of 155.423 and a significance of 0.000. The coefficient of determination (R²) value of 0.791 indicates that 79.1% of the variation in employee performance can be explained by these two variables. These findings reinforce the importance of team collaboration and adaptability in improving employee performance in government agency environments. Therefore, organizations are advised to strengthen teamwork culture and develop employee adaptive capabilities in order to achieve organizational goals optimally.